Emotion and Value in the Evaluation of Medical Decision-Making Capacity: A Narrative Review of Arguments - Hermann, Helena; Trachsel, Manuel; Elger, Bernice S.; Biller-Andorno, Nikola (Frontiers in Psychology, 2016)
Ever since the traditional criteria for medical decision-making capacity (understanding, appreciation, reasoning, evidencing a choice) were formulated, they have been criticized for not taking sufficient account of emotions or values that seem, according to the critics and in line with clinical experiences, essential to decision-making capacity. The aim of this paper is to provide a nuanced and structured overview of the arguments provided in the literature emphasizing the importance of these factors and arguing for their inclusion in competence evaluations. Moreover, a broader reflection on the findings of the literature is provided. Specific difficulties of formulating and measuring emotional and valuational factors are discussed inviting reflection on the possibility of handling relevant factors in a more flexible, case-specific, and context-specific way rather than adhering to a rigid set of operationalized criteria.